2011
DOI: 10.1097/ta.0b013e3181fec9ba
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Preventable Trauma Deaths and Opportunities for Trauma Care Improvement in Utah

Abstract: The preventable death rate from trauma demonstrated in Utah is similar to that found in other settings where the trauma system is under development but has not reached full maturity. OFIs predominantly exist in the ED and relate to airway management, fluid resuscitation, and chest injury management. Resource organization and education of ED primary care providers in basic principles of stabilization and initial treatment may be the most cost-effective method of reducing preventable deaths in this mixed urban a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 11 publications
5
57
3
4
Order By: Relevance
“…Certainly preventable deaths in Limb's study in England were reported to be 1-2%, in Sandall's study in the USA this was 0.7%, and in Falconer's study in New Zealand this was 10%. Thus, the rate in our study was the highest (8,17,18). Hussain and Redmond (9) declared the total rate of pre-hospital preventable deaths in England to be 39%, Mac Leod to be 7%, Mark Gunst to be 24%, Wilson in Brazil to be 1%, Meel to be 12% and Flaconer's in Newsland to be 45% (7,10,12,13,17).…”
Section: Discussionmentioning
confidence: 89%
“…Certainly preventable deaths in Limb's study in England were reported to be 1-2%, in Sandall's study in the USA this was 0.7%, and in Falconer's study in New Zealand this was 10%. Thus, the rate in our study was the highest (8,17,18). Hussain and Redmond (9) declared the total rate of pre-hospital preventable deaths in England to be 39%, Mac Leod to be 7%, Mark Gunst to be 24%, Wilson in Brazil to be 1%, Meel to be 12% and Flaconer's in Newsland to be 45% (7,10,12,13,17).…”
Section: Discussionmentioning
confidence: 89%
“…The study was not designed to demonstrate whether any deaths could have been prevented by faster access to EMS. However, the proportion of deaths judged to have been preventable has varied from 7 to 15% in different studies, indicating how early recognition of severely injured patients, and appropriate therapeutic interventions are important components in pre‐hospital trauma care 32, 33…”
Section: Discussionmentioning
confidence: 99%
“…Chiara et al [4] suggested professional panel study, TRISS, and ICISS as a method of assessing preventable mortality rate. Professional panel study is a method widely used with long history [5,11]. However, during the initial working phase, it has a disadvantage of being subjective, which makes it not suitable for deciding the quality improvement in a single trauma center.…”
Section: Discussionmentioning
confidence: 99%
“…For this assessment, trauma and injury severity score (TRISS), International Classification of Disease-9 based injury severity score (ICISS), and professional panel study are widely used methods [4,5].…”
Section: Introductionmentioning
confidence: 99%